The Effect of Antenatal Care Service Utilization on Postnatal Care Service Utilization: A Systematic Review and Meta-analysis Study - Alehegn Bishaw Geremew; Moges Muluneh Boke; Ayenew Engida Yismaw (Hindawi Limited, 2020)
Introduction. Reduction of maternal and neonatal morbidity and mortality has continued to be a challenge in developing countries. The majority of maternal and neonatal mortality occurred during the early postpartum period. This is mostly due to low postnatal care service utilization. There is a discrepancy of evidence on the effect status of antenatal care on the improvement of postnatal care service utilization. Therefore, this review study is aimed at estimating the pooled effect of antenatal care on postnatal care service utilization. Methods. We searched from PubMed and Cochrane library database, Google Scholar, and Google. Initially, we found 265 articles; after duplication was removed and screened by the relevance of the titles and abstracts, 36 studies were considered for assessment of eligibility. Finally, 14 articles passed the inclusion and exclusion criteria and are included in the meta-analysis. Study quality assessment was done using Janna Briggs Institute (JBI) critical appraisal tools. The main information was extracted from each study. Heterogeneity of studies was assessed using I2=70% and more considered having high heterogeneity. The publication bias was checked using funnel plot and big test. Meta-analysis using a random effect model was conducted. A forest plot was used to show the estimated size effect of odds ratio with a 95% confidence interval. Results. A total of 14 articles were included with 15,765 participants for synthesis and meta-analysis. We found that a pooled estimate of women who had antenatal care was 1.53 times more likely to have postnatal care compared with those who had no antenatal care (AOR=1.53, 95% CI 1.38-1.70, I2=0%). Conclusions. This review results revealed a low utilization of postnatal care service. Antenatal care service utilization has a positive effect on postnatal care service utilization. Policymakers and programmers better considered more antenatal care service use as one strategy of enhancing the utilization of postnatal care service.